Use and monitoring of low dose rituximab in myasthenia gravis. Issue 6 (11th November 2010) - Blum, Stefan; Gillis, David; Brown, Helen; Boyle, Richard; Henderson, Robert; Heyworth-Smith, David; Hogan, Patrick; Kubler, Paul; Lander, Cecilie; Limberg, Nicole; Pillans, Peter; Prain, Kerri; et al.
Abstract : Background: Myasthenia gravis is an autoimmune disorder of the neuromuscular junction. Rituximab (RTX), a monoclonal antibody to CD20, leads to B lymphocyte depletion and has been used in some autoimmune disorders, including small case series of myasthenia gravis patients. Methods: A retrospective analysis was performed of all patients with acetylcholine receptor (AChR) (11 subjects) or muscle specific kinase antibody (MuSK) positive myasthenia gravis (three subjects), who had been treated with RTX in Brisbane, Australia. In most patients 1 g of RTX, in two divided doses, was given. Patients were monitored by serial clinical assessments, flow cytometry of peripheral blood B lymphocytes and antibody testing. Results: RTX led to a significant improvement in symptoms in 11 of 14 patients. Doses of immunosuppressive medications were able to be reduced in 12 of 14 patients but medications could be completely ceased in only one patient. A demonstrable reduction of autoantibody levels was found in only three AChR positive patients and one MuSK positive patient, independent of clinical improvement. Peripheral blood B lymphocyte depletion was achieved in 13 out of 14 patients. B lymphocyte recovery occurred between 9 and 30 months post RTX (median 12.3 months) and was consistently associated with worsening of clinical symptoms. Conclusion: Rituximab at a dose of 1 g appears to be beneficial in the treatment of patients with severe myasthenia gravis. Serial monitoring of peripheral blood B lymphocytes appears to be useful in guiding the need for further RTX therapy.